The criminal entraña of the sicario. Criminological aspects of the executor in a homicide by mandate - Alcalde Muñoz, Elvis Jorge (2019)
This article gives a criminological perspective on hired killers in our country, in a special way shows the main psychosocial characteristics of the person who provides his "criminal work" in exchange for a benefit, generally economic, which reveals his lack of appreciation for the life of their peers and the generalized reproach of a society hungry for justice and drastic penal sanctions against crime. On the other hand, it addresses the problem of informal control systems, preventive work by the State and the importance of strengthening the formation ofthe individual through the family and primary social environments. The methodology to be used in the present work has theoretical nuances, referred to the academic field related to Criminology, analytical, deductive, and explanatory.